Viable Adrenal Medullary Transplants in Non-Human Primates: Increasing the Number of Grafts. (1992) - Dubach, Mark
Abstract : The robust survival of stereotaxic adrenal medullary autografts in monkey brain parenchyma depends heavily on technique/11/. One aspect of technique critical for clinical applications of CNS grafting is the problem of spreading treatment effects throughout large regions in a primate brain. Stereotaxic placement of a large number of grafts, which would address this problem, would require that later grafts retain the capacity for viability over a long period of time during the surgery, while earlier grafts are being made. In the present experiments involving 12 longtailed macaques ( Macaca fascicularis ), some grafts remained in medium 2.5 h before being transplanted, without apparent loss of viability. clinically sufficient distribution of graft tissue would also require a large number of separate grafts to be derived from one adrenal medulla. One method for subdividing the gland might be to cut it into numerous very small pieces, but various dicing techniques described in this report have yielded little viable graft tissue. On the other hand, the number of ribbon grafts of the original dimensions available from a single gland is rather small; adrenal ribbons of the original dimensions were therefore further dissected. Half-length and half-width ribbons were successful, but less so than full-size ribbons in terms of proportionate viability. An assay of behavioral effectiveness, applied to all subjects described here, is presented in a separate contribution/9/.